Weight gain in Chinese youth during a 4-month COVID-19 lockdown: a retrospective observational study - Dun, Yaoshan; Ripley-Gonzalez, Jeffrey W.; Zhou, Nanjiang; You, Baiyang; Li, Qiuxia; Li, Hui; Zhang, Wenliang; Thomas, Randal J.; Olson, Thomas P.; Liu, Jie; Dong, Yuchen; Liu, Suixin (BMJ open, 2021)
ObjectivesTo observe the weight change in Chinese youth during a 4-month COVID-19 lockdown, and the association between weight change and mental health, physical activity and sedentary time changes, and dietary habits.DesignA retrospective observational study.SettingsTwo universities located in Zhejiang and Hunan provinces, China.ParticipantsThis study enrolled 12 889 college students whose body weight was measured before the lockdown (1 December 2019–20 January 2020) at the two universities, and reported their weight measured at home or community after the end of the lockdown (1–23 May 2020) via an online follow-up questionnaire.Primary and secondary outcome measuresThe primary outcome was the weight change in Chinese youth during a 4-month lockdown resulting from the COVID-19 pandemic. The secondary outcomes were the relationships of weight change to COVID-19-related stress, depression, anxiety, physical activity and sedentary time changes, and dietary habits.ResultsParticipants’ ages ranged from 17 to 27 years (M=19, SD=1) with 80.2% identified as female. The average absolute and relative changes in body weight were 2.6 (95% CI 2.0 to 3.2)) kg and 4.2% (95% CI 4.0% to 4.3%) for men, and 2.1 (1.9 to 2.4) kg and 4.2% (95% CI 3.9% to 4.4%) for women. An increase in overweight and obese individuals according to Asian cut-off points as a demographic percentage by 4.5% and 2.7% and 4.8% and 3.4% in men and women, respectively (P<0.001), was observed. Weight gain was significantly associated with increased sedentary time and an increase in COVID-19-related stress and depression score.ConclusionThe present study’s results suggest that the risk of weight gain in Chinese youth during the lockdown increased and that strategies to decrease sedentary time and improve mental health may be warranted to mitigate weight gain during and after the COVID-19 pandemic.